2021
DOI: 10.3390/ijms22179332
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation as a Critical Aspect of Blood Platelet Mitochondrial Respiration Measurements—The Impact of Platelet Activation on Mitochondrial Respiration

Abstract: Blood platelets are considered as promising candidates as easily-accessible biomarkers of mitochondrial functioning. However, their high sensitivity to various stimulus types may potentially affect mitochondrial respiration and lead to artefactual outcomes. Therefore, it is crucial to identify the factors associated with platelet preparation that may lead to changes in mitochondrial respiration. A combination of flow cytometry and advanced respirometry was used to examine the effect of blood anticoagulants, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Interestingly, the decrease in oxygen consumption (corresponding to ROUTINE respiration) was already observed for 10 μM metformin [ 12 ]. Probably, the effects of such a long incubation period could drastically reduce platelet mitochondrial respiration, as observed elsewhere [ 19 ], and at the same time increase the impact of metformin on mitochondrial electron transfer system, and thus also on mitochondrial respiration. In contrary to us, no platelet activation parameters were assessed by Protti et al [ 12 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, the decrease in oxygen consumption (corresponding to ROUTINE respiration) was already observed for 10 μM metformin [ 12 ]. Probably, the effects of such a long incubation period could drastically reduce platelet mitochondrial respiration, as observed elsewhere [ 19 ], and at the same time increase the impact of metformin on mitochondrial electron transfer system, and thus also on mitochondrial respiration. In contrary to us, no platelet activation parameters were assessed by Protti et al [ 12 ].…”
Section: Discussionmentioning
confidence: 69%
“…However, their study used a much longer incubation time. Since long-term storage adversely affects mitochondrial respiration and leads to artefactual platelet activation [ 19 ], a shorter incubation period was used in our present study. There are also several reports in the literature on the effect of metformin in vitro on other processes related to platelet functioning, such as platelet adhesion [ 21 ], platelet aggregation [ 21 , 22 ], thrombus formation [ 23 ] or thromboxane production [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of added Ca +2 in the apheresis solution, SSP+ PLT additive solution, residual calcium from the donor’s plasma could still be present in the PA samples, and even though we used two different systems for PA, we did not observe any significant differences between them (data not shown). These results indicated that the choice of medium for storage and the further respirometric measurements might be key considerations when using PLT as a biomarker of mitochondrial changes as suggested by Siewiera et al [ 46 ].…”
Section: Discussionmentioning
confidence: 77%
“…10,15 In addition, pre-analytical factors are also an important consideration when examining plasma biomarker results. 16,17 While EDTA is considered the gold standard for anti-coagulant for plasma A/T/N analyses 18 , it may interfere with other measures including functional mitochondrial outcomes 19 . In addition, anticoagulants such as acid citrate dextrose (ACD) have been shown to improve outcomes for studies focused on microparticles, such as extracellular vesicles, without interfering with downstream protein or RNA analyses.…”
Section: Introductionmentioning
confidence: 99%